👤

Find the value of /s of k so that 2k-3,k+1 and 4k+1 will form a geometric sequence​

Sagot :

The value of k so that the terms forms a geometric sequence is

\begin{gathered}\rm 1.~k=\dfrac{1}{3}\\\\2.~k=5\end{gathered}

1. k=

3

1

2. k=5

Further explanation

Geometric sequences are series of numbers that have a constant ratio

or can be interpreted:

Each number is obtained by multiplying the previous number by a constant

The sequence can be:

\rm a,ar,ar^2,ar^3,ar^4 ... etc.a,ar,ar

2

,ar

3

,ar

4

...etc.

Can be formulated for xn

\boxed{\bold{x_n=ar^{(n-1)}}}

x

n

=ar

(n−1)

where:

a is the first term, and

r is common ratio

There are 3 ways to solve quadratic equations

factoring

perfect squared

quadratic formula

The terms k-3,k+1,and 4k-2 form a geometric sequence if

\rm \dfrac{k+1}{k-3}=\dfrac{4k-2}{k+1}

k−3

k+1

=

k+1

4k−2

we multiply in cross so that we will get the quadratic equation

\begin{gathered}\rm (k-3)(4k-2)=(k+1)(k+1)\\\\4k^2-14k+6=k^2+2k+1\\\\3k^2-16k+5=0\end{gathered}

(k−3)(4k−2)=(k+1)(k+1)

4k

2

−14k+6=k

2

+2k+1

3k

2

−16k+5=0

We solve this equation by factoring

For ax²+bx+c = ax²+ px+qx+c

pq = ac and p+q = b

So :

\begin{gathered}\rm 3k^2-16k+5=0\\\\3k^2-15k-k+5=0\Rightarrow p=-15,\:q=-1,\:a=3,\:c=5\\\\3k(k-5)-1(k-5)=0\\\\(3k-1)(k-5)=0\\\\3k-1=0\Rightarrow k=\boxed{\bold{\dfrac{1}{3}}}\\\\k-5=0\Rightarrow k=\boxed{\bold{5}}\end{gathered}

3k

2

−16k+5=0

3k

2

−15k−k+5=0⇒p=−15,q=−1,a=3,c=5

3k(k−5)−1(k−5)=0

(3k−1)(k−5)=0

3k−1=0⇒k=

3

1

k−5=0⇒k=

5

Learn more

the geometric sequence

https://brainly.ph/question/154960

Formula for geometric sequence

https://brainly.ph/question/2238923

Geometric

#BetterWithBrainly

hope it's help

#carry on learning buddy